Committee chamber, New-York, November 3d, 1775 : Whereas the Provincial Congress, in order that the duration of their power might be limited to a short period . - Remsen, Henry, 1736-1792; Philelutheros; Holt, John, 1721-1784 (LLMC-digital (Series), 1775)
Announcing that representatives to the Provincial Congress are to be elected in May of 1776, and nominating a slate of candidates.